Characterization of a single reporter-gene potency assay for T-cell-dependent bispecific molecules - Ho Young Lee; Ames Register; Jeongsup Shim; Edward Contreras; Qiang Wu; Guoying Jiang (Taylor & Francis Group, 2019)
T-cell-dependent bispecific antibodies (TDBs) are promising cancer immunotherapies that recruit patients' T cells to kill cancer cells. There are many TDBs in clinical trials, demonstrating their widely recognized therapeutic potential. However, their complex, multi-step mechanism of action (MoA), which includes bispecific antigen binding, T-cell activation, and target-cell killing, presents unique challenges for biological characterization and potency assay selection. Here, we describe the development of a single reporter-gene potency assay for a TDB (TDB1) that is MoA reflective and sensitive to binding of both antigens. Our reporter-gene assay measures T-cell activation using Jurkat cells engineered to express luciferase under the control of an NFkB response element. The potencies of select samples were measured both by this assay and by a flow-cytometry-based cell-killing assay using human lymphocytes as effector cells. Correlating the two sets of potency results clearly establishes our reporter-gene assay as MoA reflective. Furthermore, correlating potencies for the same panel of samples against binding data measured by binding assays for each individual arm demonstrates that the reporter-gene potency assay reflects dual-antigen binding and can detect changes in affinity for either arm. This work demonstrates that one reporter-gene assay can be used to measure the potency of TDB1 while capturing key aspects of its MoA, thus serving as a useful case study of selection and justification of reporter-gene potency assays for TDBs. Furthermore, our strategy of correlating reporter-gene potency, target-cell killing, and antigen binding for each individual arm serves as a useful example of a thorough, holistic approach to biological characterization for TDBs that can be applied to other bispecific molecules.